2021
DOI: 10.20396/bjos.v20i00.8663641
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of self-adhesive flowable resin composites to tooth structure

Abstract: Aim: To review the current literature regarding the bond strength of self-adhesive flowable resin composites (SAFRCs) to tooth structure, comparing the outcomes with conventional flowable resin composites (CFRCs). Methods: PubMed/Medline, EbscoHost and Scopus databases were screened (last update on November 2020) using related Medical Subject Headings (MeSH) and free terms. We included in vitro studies published in English language comparing the bond strength of SAFRCs and CFRCs to enamel and/or dentin from pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The results of this study also correspond with a systematic review conducted by Troconis and Pérez [25], while the results of this study differed from the study of Sachdeva et al, which showed no significant differences in terms of the microleakage because they did not perform thermocycling before applying the dye penetration [26].…”
Section: Discussionsupporting
confidence: 77%
“…The results of this study also correspond with a systematic review conducted by Troconis and Pérez [25], while the results of this study differed from the study of Sachdeva et al, which showed no significant differences in terms of the microleakage because they did not perform thermocycling before applying the dye penetration [26].…”
Section: Discussionsupporting
confidence: 77%
“…However, these systems, featuring several or just one application step, are still technique-sensitive and prone to degradation owing to their hydrophilic nature [1]. For this reason, following the trend of simplifying procedures, there is a need to find new, efficient, and long-lasting alternatives in the field of restorative dentistry [2,3]. The Minamata Convention in 2013, which phased out amalgam use, sparked the drive to research new general-purpose dental restorative materials with competitive properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…These can be glycerophosphate dimethacrylate (GPDM) or 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP), which promote self-etching features and chemical bonding potential [7]. Enriching SACs with functional monomers is intended to establish chemical adhesion following superficial etching without requiring an adhesive system [3,[8][9][10]. This simplification aims to reduce the variability in the bonding procedure, the risk of clinical errors (because fewer steps are needed), the need for moisture control, and eventually also reduce postoperative sensitivity [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations